1995
DOI: 10.1097/00000658-199501000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Ventilation Improves Pulmonary Function, Gas Exchange, and Lung Injury in a Model of Respiratory Failure

Abstract: In a model of severe respiratory failure, LV improves pulmonary gas exchange and compliance with an associated reduction in alveolar hemorrhage, edema, and inflammatory infiltrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(52 citation statements)
references
References 18 publications
2
46
0
4
Order By: Relevance
“…70,81,83,107,108 The foundation for this approach is related to removal of the caustic substance (i.e., meconium) or alveolar fluid accumulation. In a group of meconium-stained preterm lambs, poor oxygen exchange, acidosis, and low pulmonary compliance was present at birth and during CMV.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…70,81,83,107,108 The foundation for this approach is related to removal of the caustic substance (i.e., meconium) or alveolar fluid accumulation. In a group of meconium-stained preterm lambs, poor oxygen exchange, acidosis, and low pulmonary compliance was present at birth and during CMV.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…93,94 In another study, severe respiratory failure was induced with oleic acid in young sheep. 95 Improved pulmonary mechanics (increased compliance), improved oxygenation, and marked reduction in alveolar haemorrhage, lung fluid accumulation and inflammatory infiltration was demonstrated in the PFOB group, as compared to the gas ventilated animals. A human adult trial found significant improvement in physiological shunt and static pulmonary compliance.…”
Section: Partial Liquid Ventilation With Fluorocarbons: Improvement Omentioning
confidence: 89%
“…A VLP, quando comparada com ventilação convencional, apresenta impacto positivo na sobrevida e melhora da arquitetura pulmonar, com redução das alterações histológicas e morfológicas em modelos de lesão pulmonar aguda (54,55) . (56) , hemorragia e inflamação (57) .…”
Section: J Pneumol 28(6) -Nov-dez De 2002unclassified
“…Recentemente, a ventilação líquida parcial com perfluorocarbono tem sido uma alternativa para a ventilação mecânica convencional no manejo da SDRA (54,55) . Os perfluorocarbonos funcionam como uma PEEP líqui-da, por manterem os alvéolos abertos durante a lesão pulmonar.…”
Section: J Pneumol 28(6) -Nov-dez De 2002unclassified